Sengketa Mahar Setelah Perceraian - Nur Annisa Asjaksaan; Zainuddin Zainuddin; Rustan Rustan; Muhammad Said P (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2020)
The right of a woman to accept a marriage dowry from the groom is full of acceptance, indicating that the transfer of property is perfect for the woman he marries, but the phenomenon in the society of a region still makes it a dispute that shows different definitions and categories of dowries. This article analyzes the law related to judges' legal considerations in resolving dowry disputes that have not been cashed after divorce in a court decision. Normative research methods using literature law materials are used as an approach in the legal analysis of this article and a court decision. The results of the legal analysis of dowry disputes after divorce can be seen from 2 (two) aspects, namely the aspect of the dispute resolution process with the claims in a reconciliation suit in a divorce case, and the legal consideration aspects of judges in an incremental case and become a jurisprudence in overcoming problems similar. The dowry that has not been cash since the marriage as the originator of the dispute uses a civil procedural law approach within the scope of religious courts as well as dispute resolution in general courts, and additional requirements are required in completing the administration of marriage applications at the Office of Religious Affairs so that a dowry dispute after divorce becomes a preventive step. Abstrak:Hak perempuan menerima mahar perkawinan dari mempelai pria dengan penuh kerelaan, menunjukkan bahwa peralihan sesuatu harta benda secara sempurna kepada perempuan yang dinikahinya, namun fenomena dalam masyarakat suatu wilayah masih saja menjadikannya sebuah sengketa yang menunjukkan definisi berbeda dan ketegori tentang mahar. Artikel ini menganalisis hukum terkait pertimbangan hukum hakim dalam menyelesaikan sengketa mahar yang belum tunai setelah perceraian pada sebuah putusan pengadilan. Metode penelitian normatif dengan menggunakan bahan hukum kepustakaan digunakan sebagai pendekatan dalam analisis hukum artikel ini, dan sebuah putusan pengadilan. Hasil analisis hukum sengketa mahar setelah perceraian dapat dilihat dari 2 (dua) aspek, yaitu aspek proses penyelesaian sengketa dengan komulasi gugatan dalam gugatan rekonvensi pada perkara cerai talak, dan aspek pertimbangan hukum hakim dalam sebuah kasus yang inkracht dan menjadi sebuah yurisprudensi dalam mengatasi masalah yang serupa. Mahar yang belum tunai sejak pernikahan sebagai pencetus sengketa menggunakan pendekatan hukum acara perdata diruang lingkup pengadilan agama sebagaimana penyelesaian sengketa diperadilan umum, dan diperlukan syarat tambahan dalam melengkapi administrasi permohonan pernikahan di Kantor Urusan Agama agar sengketa mahar setelah perceraian menjadi sebuah langkah preventif.